Valorização da negociação coletiva atípica como instrumento de promoção de liberdade sindical - Medeiros, Gustavo Jonasson de Conti (2023)
The study analyzes the principles that guide collective bargaining as a skillful instrument for resolving conflicts between workers and employers. It explores the process for establishing the negotiation process, pointing out some obstacles imposed by Brazilian legislation to the exercise of freedom of association. It studies the roles exercised by unions and identifies some new challenges due to the modernization of labor relations. It observes the possibility of dual collective representation of workers and, in the end, points out an alternative that allows the maximum effectiveness of constitutionally guaranteed rights